Eating Alone Yet Living With Others Is Associated With Mortality in Older Men: The JAGES Cohort Survey. (16th January 2017) - Tani, Yukako; Kondo, Naoki; Noma, Hisashi; Miyaguni, Yasuhiro; Saito, Masashige; Kondo, Katsunori
Abstract: Objectives: Eating by oneself may be a risk factor for poor nutritional and mental statuses among older adults. However, their longitudinal association with mortality in relation to coresidential status is unknown. Method: We conducted a 3-year follow-up of participants in the Japan Gerontological Evaluation Study, a population-based cohort of 65 years or older Japanese adults. We analyzed mortality for 33, 083 men and 38, 698 women from 2010 to 2013 and used. Cox regression models were used to estimate hazard ratios (HR) for mortality. Results: A total of 3, 217 deaths occurred during the follow-up. Compared with men who ate and lived with others, the HRs after adjusting for age and health status were 1.48 (95% confidence intervals [CI]: 1.26–1.74) for men who ate alone yet lived with others and 1.19 (95% CI: 1.01–1.41) for men who ate and lived alone. Among women, the adjusted HR was 1.18 (95% CI: 0.97–1.43) for women who ate alone yet lived with others and 1.10 (95% CI: 0.93–1.29) for women who ate and lived alone. Discussion: A setting in which older adults eat together may be protective for them. Promotion of this intervention should focus on men who eat alone yet live with others.